Gel dosimetry measurements and Monte Carlo modeling for external radiotherapy photon beams. Comparison with a treatment planning system dose distribution - Valente, Mauro Andres (2007)
Gel dosimetry has proved to be useful to determine absorbed dose distributions in radiotherapy, as well as to validate treatment plans. Gel dosimetry allows dose imaging and is particularly helpful for non-uniform dose distribution measurements, as may occur when multiple-field irradiation techniques are employed. In this work, we report gel-dosimetry measurements and Monte Carlo (PENELOPE®) calculations for the dose distribution inside a tissue-equivalent phantom exposed to a typical multiple-field irradiation. Irradiations were performed with a 10 MV photon beam from a Varian® Clinac 18 accelerator. The employed dosimeters consisted of layers of Fricke Xylenol Orange radiochromic gel. The method for absorbed dose imaging was based on analysis of visible light transmittance, usually detected by means of a CCD camera. With the aim of finding a simple method for light transmittance image acquisition, a commercial flatbed-like scanner was employed. The experimental and simulated dose distributions have been compared with those calculated with a commercially available treatment planning system, showing a reasonable agreement.